While law of the biopolitical - Perera, Suvendrini; Pugliese, J. (Coolabah, 2012)
Drawing on Ruby Langford Ginibi’s writings on the law throughout the 1990s we discuss how law, as an apparatus of biopolitical governmentality, frames, positions and inscribes the very sites, institutions and bodies essential to the reproduction of Australia as a racialised nation-state. The paper builds on the collective work we have done for over a decade in documenting how whiteness enmeshes with law in securing and reproducing colonial and racist forms of biopower, and its effects on the embodied subjects who are its targets: the scandal of the Tampa; the horrors of refugee suicide and self-harm in immigration prisons; the Cronulla race riots; the continuing attempts to extinguish Indigenous sovereignty; the fomenting of Islamophobia and the normalising of racial profiling; the violence of the Northern Territory Intervention; and escalating Aboriginal deaths in and out of custody. Our paper focuses on a number of current crises that evidence only too clearly the violences unleashed and licensed by white laws of the biopolitical.